PERLINDUNGAN HUKUM TERHADAP KONSUMEN GRAB FOOD BERDASARKAN KETIDAKSESUAIAN INFORMASI DALAM ETIKET GAMBAR - Ryan Axel Pattiasina, (Sekolah Tinggi Ilmu Al-Qur'an Amuntai, 2023)
Consumer protection is an important instrument because many people carry out buying and selling transactions, one of which is digital transactions. One case of consumer protection is when a buyer buys a product that is not in accordance with what is being sold and does not meet or does not comply with the standards being sold. This research examines how legal protection for Grabfood consumers is based on information discrepancies in image labels and how services in the GrabFood application are based on the right to correct, clear and honest information regarding the condition and guarantee of goods and/or services. The research method used in this research is normative, supplemented by interviews. This research uses primary and secondary legal materials, literature studies including legislation, books, legal dictionaries, journals and the internet. Based on the results of this research, consumers are obliged to receive compensation as a form of legal protection if there is a discrepancy in the information in the image label and also the service on the GrabFood application is not running well due to a lack of transparency, insight and knowledge from the service provider and also a lack of distribution and resolution of consumer complaints. , there are also obstacles in consumer protection for GrabFood services which are influenced by several factors so that they are not in accordance with article 4 paragraph 3 of Law no. 8 of 1999 concerning consumer protection.